On the Insufficiencies of the Current Legislative Regime Regarding Physician-Patient Mediation in the Professional Liability of Physicians. A Critical Analysis of the Polish Solution - Bek, Dominika; Hanc, Jakub (Medicine, Law & Society, 2023)
The article presents a critical opinion on physician- patient mediation conducted in the context of proceedings on the professional liability of physicians. The starting point is the Act on Medical Chambers, which provides for the possibility of conducting a mediation between the accused physician and the aggrieved patient. This regulation is unique in the region. Its specific measures, such as, for example, the choice of a mediator among physicians, have undergone a critical assessment in the literature. As a rule, the need for the functioning of mediation in the context of professional liability is not called into question. However, a thorough analysis of the assumptions of mediation and restorative justice and the function of professional liability of physicians suggests going a step further. Although the physician-patient conflict certainly requires conciliatory solutions, it seems that the disciplinary regime does not provide an adequate foundation for agreement because it is unable to secure the aggrieved person’s interests.